2019
DOI: 10.1021/acs.chemrev.8b00608
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Lipid–Protein Interactions and Lipid-Mediated Modulation of Membrane Protein Function through Molecular Simulation

Abstract: The cellular membrane constitutes one of the most fundamental compartments of a living cell, where key processes such as selective transport of material and exchange of information between the cell and its environment are mediated by proteins that are closely associated with the membrane. The heterogeneity of lipid composition of biological membranes and the effect of lipid molecules on the structure, dynamics, and function of membrane proteins are now widely recognized. Characterization of these functionally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
189
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 207 publications
(209 citation statements)
references
References 1,166 publications
(2,461 reference statements)
4
189
0
Order By: Relevance
“…Following the developments in hardware and software, MD simulation have increasingly begun to capture the structural dynamics of larger macromolecular systems, like ribosomes, 57 protein-membrane systems (e.g., transporters and channels), 58,59 virus membranes, 60 and lipid rafts. 32,33 By overcoming the resolution limits of the experimental methods and exploring the fine molecular details of macromolecular events, MD simulations can now serve as molecular microscope 35,61 to investigate lipid-lipid and protein-lipid interactions of more realistic cell membranes on submillisecond timescale ( Fig. 5A).…”
Section: Role Of MD Simulations In Investigating Protein-membrane Sysmentioning
confidence: 99%
See 3 more Smart Citations
“…Following the developments in hardware and software, MD simulation have increasingly begun to capture the structural dynamics of larger macromolecular systems, like ribosomes, 57 protein-membrane systems (e.g., transporters and channels), 58,59 virus membranes, 60 and lipid rafts. 32,33 By overcoming the resolution limits of the experimental methods and exploring the fine molecular details of macromolecular events, MD simulations can now serve as molecular microscope 35,61 to investigate lipid-lipid and protein-lipid interactions of more realistic cell membranes on submillisecond timescale ( Fig. 5A).…”
Section: Role Of MD Simulations In Investigating Protein-membrane Sysmentioning
confidence: 99%
“…[325][326][327] In vitro studies have shown that DHA inhibits Aβ 42 fibril formation. 328 To better understand the inhibitory role of DHA, Ntarakas et al, 323 carried out MD simulations of Aβ peptide fragments Aβ 1-28 and Aβ [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] in single component bilayers (DMPC-14:0,14:0 or SDPC-18:0,22:6) and in mixed bilayers (DSPE-18:0,18:0, DDPE-22:6,22:6, DPPC-16:0,16:0, DOPC-18:1,18:1) with varying composition. The mixed bilayer is divided into two types based on lipid composition.…”
Section: Amyloid β (Aβ) Peptidementioning
confidence: 99%
See 2 more Smart Citations
“…(54,56) In general, lipid-protein interactions are significant determinants of the membrane protein functions. (57)(58)(59)(60) It is natural and fundamental to ask: What are the dynamic characteristics of GLUT1 embedded in a membrane of inner-andouter-leaflet asymmetric lipid compositions? Furthermore, in all GLUT1 simulations of the current literature, the intracellular (IC) and the extracellular (EC) sides are artifactitiously mixed as technically required by the computing technique of electrostatic interactions.…”
Section: Introductionmentioning
confidence: 99%